Pengaruh Pengelasan Gas Tungsten Arc Welding (GTAW) Pada Uji Kebocoran Pipa Baja ASTM A106 Menggunakan Metode Uji Hydrotastic Test - Muhammad Rifki Aziz; Aa Santosa; Iwan Nugraha Gusniar (Jurnal Ilmiah Wahana Pendidikan, 2023)
ASTM A106 pipe is a type of low carbon steel pipe used for high temperature applications (up to a temperature of 750 degrees F). This type of pipe is resistant to corrosion and can withstand high fluid pressure, so it is often used in the industrial world to convey water, oil and other oils. The purpose of this study was to compare the heat input resulting from variations in welding current to the hydotest, microstructure and tensile test. The method used uses Gas Tungsten Arc Welding (GTAW) welding with current variations of 70 A, 90 A and 110 A with a Hydrostatic Test pressure of 450 Psi. The results showed that the greatest heat input occurred at a current variation of 110 A with a heat input of 1,349.05 J/mm and the lowest heat input occurred at a welding current of 70A of 1,229.72 J/mm. The results of the microstructure test with variations in GTAW welding currents formed the Ferrite-Pearlite phase as a constituent of the microstructure. The results of the tensile test on A106 steel pipe with variations in welding currents of 70A, 90A, and 110A, the highest tensile strength occurred at a welding current of 110A with a tensile strength of 46.7 N/mm and the lowest tensile strength at a current of 70A with a tensile strength of 43.85. Whereas for the Hydrostatic test with class # 150, the pressure is 1.5x design, so the maximum pressure reaches 450 Psi is carried out on 3 pipes with GTAW welding variation 3 with welding currents of 70A, 90A and 110A, declared successful because no leaks occurred during the test.